2004
DOI: 10.1158/1078-0432.ccr-03-0087
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial-Cadherin and β-Catenin Expression Changes in Pancreatic Intraepithelial Neoplasia

Abstract: Purpose: Cadherins and associated catenins are important mediators of epithelial cell-cell adhesion, as well as the Wnt-signaling pathway. Significant changes in their expression or structure have been implicated in malignancy. This study aimed to investigate the epithelial-cadherin (Ecadherin) and ␤-catenin expression changes during multistage, pancreatic ductal carcinogenesis.Experimental Design: Ninety-four Whipple resection specimens were retrieved from the surgical pathology files of the University Health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
68
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 100 publications
(76 citation statements)
references
References 30 publications
8
68
0
Order By: Relevance
“…Then, they are transferred to the cell nucleus where they bind to the transcription factors TCF/LEF-1, thus affecting the expression of target genes. Some authors have observed nuclear expression of β-catenin in pancreatic cancer, which could indicate that carcinogenesis is also associated with the Wnt pathway [17,18]. We observed a distinct loss of membranous and cytoplasmic β-catenin expression and no nuclear reaction with GSK-3β, which could suggest that the Wnt pathway had not been activated and free catenins had been degraded with GSK-3 involvement.…”
Section: Discussionsupporting
confidence: 50%
“…Then, they are transferred to the cell nucleus where they bind to the transcription factors TCF/LEF-1, thus affecting the expression of target genes. Some authors have observed nuclear expression of β-catenin in pancreatic cancer, which could indicate that carcinogenesis is also associated with the Wnt pathway [17,18]. We observed a distinct loss of membranous and cytoplasmic β-catenin expression and no nuclear reaction with GSK-3β, which could suggest that the Wnt pathway had not been activated and free catenins had been degraded with GSK-3 involvement.…”
Section: Discussionsupporting
confidence: 50%
“…ZG16p and GP2 are both major constituents of the submembranous matrix purfied from zymogen granules, potentially serving a role in protein sorting or granule formation (15). Muclin is a membrane protein present in the zymogen granule that also contains a ZP domain and has also been proposed to play a role in protein sorting (27). When quantitative protein immunoblotting was performed to compare the relative amounts of syncollin, ZG16p, and muclin to amylase in zymogen granules, there was no significant difference between wild-type and GP2-deficient mice (Fig.…”
Section: Figmentioning
confidence: 99%
“…The assays were done using Stratagene MX3000P (La Jolla, CA). The relative quantification of gene expression was determined using the comparative C T method as described previously (25)(26)(27). The values of 18S rRNA were used to normalize the expression data.…”
Section: Ink4amentioning
confidence: 99%